EMT and Cancer Cell Stemness Associated With Chemotherapeutic Resistance in Esophageal Cancer - Liu, Xiaojie; He, Mingjing; Li, Linlin; Wang, Xiya; Han, Shuhua; Zhao, Jinzhu; Dong, Yalong; Ahmad, Mushtaq; Li, Leilei; Zhang, Xueyan; Huo, Junfeng; Liu, Yunfan; et al. (Frontiers in Oncology, 2021)
Drug resistance often occurs after chemotherapy in esophageal cancer patients, leading to cancer metastasis and recurrence. However, the relationship among cancer cell migration, recurrence and drug resistance in esophageal cancer drug resistant cells has not been clearly explained. In this study, we constructed paclitaxel (PTX)-resistant esophageal cancer cells to explore the causes of drug resistance and poor prognosis after chemotherapy in esophageal cancer. Colony formation assay was used to evaluate the difference of colony formation between parental cells and drug resistance cells. Microsphere formation assay was used to examine the phenotype of stem cells. Wound healing and Transwell assays were used to detect the migration ability of drug resistant cells. Western blotting and immunofluorescence assays were used to explore the mechanisms. Finally, we used nude mouse xenograft model to explore the tumor characteristics and the expression of relative proteins to verify our findings in vivo. Our study demonstrated that the cancer cell stemness characteristics exists in drug-resistant esophageal cancer cells, that expressed the biomarkers of stem cells and were prone to EMT. Our results suggested that the expression of EMT biomarkers and stemness-related proteins increased in esophageal cancer cells after continuously using chemotherapeutic drugs for a period of time. This study indicated that simultaneously targeting EMT and stemness could be a better strategy for the treatment of esophageal cancer drug resistance.